2011
DOI: 10.1002/jwmg.225
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of anthropogenic watering sites by desert carnivores

Abstract: We investigated the role of water features as focal attractors for gray foxes (Urocyon cinereoargenteus), coyotes (Canis latrans), and bobcats (Felis rufus) in west Texas to determine if they were foci for interspecific interaction. Mixed effects models indicated that species partitioned use of water features spatially and temporally. Linear models indicated factors influencing relative activity at water features varied by species. For coyotes and bobcats, the water availability model, containing days since la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 43 publications
7
53
1
Order By: Relevance
“…Atwood et al, 2011;Hayward and Slotow, 2009;Mitchell and Banks, 2005;Ramesh et al, 2012). Because mesopredators typically seek to avoid encountering top-predators (i.e.…”
Section: Sampling Biasmentioning
confidence: 99%
“…Atwood et al, 2011;Hayward and Slotow, 2009;Mitchell and Banks, 2005;Ramesh et al, 2012). Because mesopredators typically seek to avoid encountering top-predators (i.e.…”
Section: Sampling Biasmentioning
confidence: 99%
“…Other studies have shown resource sharing of a limiting resource, such as water, with partitioning in time rather than space. For example, a study of eight carnivores in Namibia (Edwards et al 2015), and one of coyotes, bobcats (Lynx rufus), and grey foxes (Urocyon cinereoargenteus) in west Texas (Atwood et al 2011) showed that species shared water tanks through temporal partitioning. However, my results could also be explained by my supplementary analyses of the association between rocky habitats and rivers, where I detected higher terrain ruggedness (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the interactions among predators often result in spatial or temporal resource partitioning, where smaller species take suboptimal resources or time-slots to reduce the risk posed by larger ones (Atwood et al 2011;Bischof et al 2014;Brook et al 2012). …”
Section: Top-down Vs Bottom-up Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[117][118][119]). Because mesopredators typically seek to avoid encountering top-predators, mesopredator activity is likely to be lower at times and in places with higher top-predator activity.…”
Section: Sampling Biasmentioning
confidence: 99%